Segment Information Disclosure and the Cost of Equity Capital - Junwook Yoo; Igor Semenenko (Journal of Accounting, Business and Management (JABM), 2012)
This study develops an empirical proxy for the quality of segment reporting from data in corporate annual reports, and provides evidence that financial markets price the quality of segment reporting as systematic (non-diversifiable) risk. Lower segment information quality is associated with higher cost of equity capital in the cross-section of asset returns. Further, quality of reporting has larger impact on the cost of equity capital for firms with lower analyst following. Analyst coverage proxy lowers magnitude of the segment information variable, but the latter retains significance in all asset-pricing tests.